Cobalt (II)-hydroxide terephthalate - a metamagnet with a large coercive field - Lovett, B; Blundell, S; Kumagai, H; Kurmoo, M (2001)
We present the field dependent magnetization and magnetic susceptibility of an unusual metamagnet Co-2(OH)(2)(O2CC6H4CO2). It is characterized by a maximum in the susceptibility at the Neel temperature of 48 K and by spontaneous magnetization at a T-C of 43 K due to a small canting. It displays the characteristic kink of a metamagnetic transition in the field-dependent magnetization below T-N. Below T-C hysteresis is observed whose width increases to span +/- 5.2 T at 1.5 K. We propose a qualitative explanation of the rich phase behaviour.